Effect of donor parameters on primary graft failure and the recovery of acuity after keratoplasty. Issue 1 (January 1990) - Halliday, B L; Ritten, S A
Abstract : A retrospective evaluation was made of 983 penetrating corneal grafts. Donor corneas stored in either K-Sol or McCarey-Kaufman media had a significantly greater rate of primary graft failure (about 2%) than those kept in moist chamber storage (0%). Selected subgroups of 50 corneas from each storage system were studied to determine the time taken to reach a postoperative acuity of 6/12. No significant correlation was found between this time and either the duration of storage of donor corneas or the age of donor. A significant delay in recovery of visual acuity was found with increasing age of recipient. The increased average time from donor death to surgery for K-Sol (56 hours) and McCarey-Kaufman (40 hours) corneas compared with moist chamber corneas (15 hours) facilitated the scheduling of surgery at the cost of increased chance of primary graft failure.